Flexible Light‐to‐Frequency Conversion Circuits Built with Si‐Based Frequency‐to‐Digital Converters via Complementary Photosensitive Ring Oscillators with p‐Type SWNT and n‐Type a‐IGZO Thin Film Transistors. Issue 26 (9th May 2021) - Jeong, Jinheon; Seo, Seung Gi; Yu, Seung‐Myeong; Kang, Yunha; Song, Junyoung; Jin, Sung Hun
Abstract: In this study, as system‐level photodetectors, light‐to‐frequency conversion circuits (LFCs) are realized by i) photosensitive ring oscillators (ROs) composed of amorphous indium‐gallium‐zinc‐oxide/single‐walled carbon nanotube (a‐IGZO/SWNT) thin film transistors (TFTs) and ii) phase‐locked‐loop Si circuits built with frequency‐to‐digital converters (PFDC). The 3‐stage ROs and logic gates based on a‐IGZO/SWNT TFTs successfully demonstrate its performance on flexible substrates. Herein, along with the advantage of scalability, a‐IGZO films are used as photosensitive n‐type TFTs and SWNTs are employed as photo‐insensitive p‐type TFTs for better photosensitivity in circuit level. Through the controlling a post‐annealing condition of a‐IGZO film, responsivities and detectivities of a‐IGZO TFTs are obtained as 36 AW −1 and 0.3 × 10 12 Jones for red, 93 AW −1 and 3.1 × 10 12 Jones for green, and 194 AW –1 and 11.7 × 10 12 Jones for blue. Furthermore, as an advanced demonstration for practical application of LFCs, a unique circuit (i.e., PFDC) is designed to analyze the generated oscillation frequency ( f osc ) from the LFC device and convert it to a digital code. As a result, the designed PFDC can exactly count the generated f osc from the flexible a‐IGZO/SWNT ROs under light illumination with an outstanding sensitivity and assign input frequencies to respective digital code. Abstract : As a system‐level photodetector, light‐to‐frequency conversion circuit (LFC) is implemented on the flexible substrate using amorphous indium‐gallium‐zinc‐oxide and single walled carbon nanotubes thin‐film transistors. As an advanced demonstration for practical application, CMOS‐based frequency‐to‐digital converter is realized for digitization of analog signal from LFC. With better noise immunity, proposed systems will contribute to the newly conceived Internet‐of‐Things sensor systems.